The Influence of Teacher Competence and Work Motivation on the Performance of State High School Teachers - Halimahturrafiah, Nur; Marsidin, Sufyarma; Anisah; Rifma (Journal of Education Reseach and Evaluation, 2023)
There are still problems related to teacher performance which are thought to be caused by teacher competence and low work motivation. The purpose of this study was to analyze about (1) the performance of state high school teachers. (2) the competence of state high school teachers. (3) the work motivation of state high schools. (4) the influence of teacher competence and work motivation in partial and joint performance on the performance of State High School teachers. This research is correlational quantitative research with associative type. The population is all teachers who teach at State High School, totaling 191 people. Samples were taken using the Proportional Stratified Random Sampling technique. The research instrument used a Likert Scale model questionnaire. From the trial results, it was found that the research questionnaire was valid. Then the research data were analyzed using the average score (Mean) for data description, requirements test, namely the normality test, homogeneity test, linearity test and multicollinearity test. Then test the hypothesis using simple linear regression and multiple linear regression testing using SPSS version 25.0. The results of the descriptive analysis of teacher performance were 89.40%, teacher competence was 89.95%, and work motivation was 87.9%. The results of the data analysis show that there is a significant influence between teacher competence on teacher performance of 47.2%, there is a significant influence between work motivation on teacher performance of 25.8%, and there is a significant influence between teacher competency and work motivation jointly on teacher performance of 75.1%.